Intravenous lipid emulsion in treatment of cardiocirculatory disturbances caused by glyphosate-surfactant herbicide poisoning - Jović-Stošić, Jasmina; Putić, Vesna; Perković-Vukčević, Nataša; Babić, Gordana; Djordjević, Snežana; Šegrt, Zoran (Vojnosanitetski pregled, 2017)
Introduction. Glyphosate is the first widely used herbicide against weed in genetically modified crops. Though glyphosate itself has a low toxicity, commercial products are more dangerous because of increased toxicity due to surfactants addition. There is no specific antidote for the poisoning with glyphosate-surfactant (Gly-SH). In recent times, the efficacy of intravenous lipid emulsion (ILE) administration for the treatment of acute poisoning caused by Gly-SH has been investigated. Case Report. A 50-year-old man was admitted 3 h after self-poisoning with herbicide containing glyphosate and polyoxyethyleneamine, as a surfactant. On admission, the patient was in a coma, hypotensive (80/50 mmHg) and without spontaneous breathing. Electrocardiogram showed wide-complex tachycardia, and arterial blood gas (ABG) revealed acidosis (pH 7.07). Conventional treatment included mechanical ventilation, intravenous fluids, bicarbonate and dopamine. As there was no improvement, ILE was started. The patient received 100 mL of 20% Intralipid® bolus followed by infusion of 400 mL over 20 minutes. Prior to expiration of infusion, a gradual rise in blood pressure was noted, and within 2 hours sinus rhythm was restored. Conclusion. This case report suggests that the use of ILE may be an additional option for the treatment of cardiocirculatory disturbances caused by commercial products of glyphosate herbicide.